Cancer Control and Oncology Care in Iraq - Al Alwan, Nada A S (Journal of Contemporary Medical Sciences, 2022)
This country report focuses on the cancer control and oncology services in Iraq. This report displaying the approaches that are made to implement the elements of the national cancer control program including cancer registration, prevention, early detection, treatment, palliative care and research.